FUNCTIONAL NEUROIMAGING STUDIES IN POSTTRAUMATIC STRESS DISORDER: REVIEW OF CURRENT METHODS AND FINDINGS - Francati, V. (2007)
Posttraumatic stress disorder (PTSD) is an anxiety disorder associated with changes in neural circuitry involving frontal and limbic systems. Altered metabolism in these brain structures after a traumatic event is correlated to PTSD. Developments in the field of neuroimaging have allowed researchers to look at the structural and functional properties of the brain in PTSD. Despite the relative novelty of functional imaging and its application to the field of PTSD, numerous publications have brought to light several of the circuits implied in this disorder. This article summarizes the findings with regard to PTSD in the functional imaging techniques of single-photon emission computed tomography (SPECT), positron emission tomography (PET), and functional magnetic resonance imaging (fMRI). Furthermore, we discuss strengths and weaknesses of the various techniques and studies. Finally, we explore the future potential of functional neuroimaging studies in PTSD.